Pengaruh Metode Pembelajaran Berbasis Proyek Kerajinan Gerabah Terhadap Kreativitas Anak Usia Dini - Diah Alfina Febrianti; Ratno Abidin; Tri Kurniawati; Naili Sa’ida (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Learning methods are the methods used to implement learning plans which are prepared in the form of real and practical activities to achieve learning objectives. In order for the learning process to be effective and enjoyable, learning methods must be varied and appropriate to the child's development. However, research in the field shows that the learning methods most often used by teachers are monotonous and uninteresting. Creativity is very important in early childhood education because children's cognitive development will be honed if they are creative. This is because creativity increases their intelligence and ability to express themselves and develop new ideas. . The pottery craft project-based learning method is suitable for the learning process in early childhood because it is interesting. This research aims to see how much influence this learning method has on the creativity of young children. This research uses quantitative research methods, with a one group pretest-posttest design, data analysis techniques using the Wilcoxon sign rank test. The results of this test show that each subject experienced an increase in aspects of their creativity, for example, children began to be able to produce an idea, children were able to create or combine unique and interesting works in front of other people, children were able to create or produce their own work without copying the theme, and without Of course, children are able to develop new works, and children are also able to improve the details of their own work, apart from that, children also feel happy and not bored because learning using this pottery craft project-based method is very interesting and suitable for application in children's learning.